2022
DOI: 10.3390/ijerph19063347
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Breastfeeding during the COVID-19 Pandemic: A Scoping Review of Perinatal Care Recommendations in the Context of Maternal and Child Well-Being

Abstract: The objective of this scoping review is to determine to what extent the recommendations on perinatal care protect breastfeeding during the COVID-19 pandemic. The review follows the PRISMA ScR Extension guidelines. The research was conducted in Scopus, Medline via Pubmed, and Web of Science databases from 1 March 2020 to 31 May 2021, using 392 combinations of keywords. We searched for reviews and original papers published in English providing recommendations on delivery mode, companion during labor, the possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 124 publications
(470 reference statements)
0
4
0
1
Order By: Relevance
“…If the diagnosis of infection in the newborn is confirmed, isolation from the mother is no longer necessary. Breastfeeding is encouraged in these cases if maternal and neonatal health allow it [ 30 ]. In the three cases presented, the newborns were moved together with the mothers after establishing the diagnosis of infection in neonates because the symptoms were minor or moderate.…”
Section: Discussionmentioning
confidence: 99%
“…If the diagnosis of infection in the newborn is confirmed, isolation from the mother is no longer necessary. Breastfeeding is encouraged in these cases if maternal and neonatal health allow it [ 30 ]. In the three cases presented, the newborns were moved together with the mothers after establishing the diagnosis of infection in neonates because the symptoms were minor or moderate.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown that the coronavirus pandemic has exerted a significant impact on delivery care and breastfeeding, highlighting the global benefits of ensuring that mothers and newborns are not separated despite the uncertainty and limited knowledge about COVID-19, along with the essential support for breastfeeding mothers, which allows achieving science-based results. The presence of barriers and/or difficulties in the provision of Nursing and Obstetrics care was also evident during the COVID-19 pandemic, including breastfeeding support (1,28,29,30,31,32,33,34,35).…”
Section: Fear and Apprehension During Hospitalization Of A Childmentioning
confidence: 99%
“…Preporuke većeg broja zemalja, koje su se odnosile na SSC tokom pandemije kovida 19, u većini studija opisane su kao nošenje hirurške maske, dezinfekcija ruku i kontaktnih površina. Iako je uglavnom bilo dozvoljeno sprovođenje SSC tokom pandemije, predlagano je pojedinačno ispitivanje postojanja kliničkih i administrativnih uslova za sprovođenje same metode (46).…”
Section: Kovid 19 I Sscunclassified